2012
DOI: 10.1186/1471-2202-13-43
|View full text |Cite
|
Sign up to set email alerts
|

ERP correlates of social conformity in a line judgment task

Abstract: BackgroundPrevious research showed that individuals have a natural tendency to conform to others. This study investigated the temporal characteristics of neural processing involved in social conformity by recording participants’ brain potentials in performing a line judgment task. After making his initial choice, a participant was presented with the choices of four same-sex group members, which could be congruent or highly or moderately incongruent with the participant’s own choice. The participant was then im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
64
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 37 publications
13
64
2
1
Order By: Relevance
“…However, it is very unlikely that the vocalization-listening difference of ERPs would be specific to participants’ language experience. Several recent neurophysiological studies have demonstrated that cortical responses to mid-utterance PSS during active vocalization are enhanced relative to passive listening in either English or Mandarin participants [28], [29], [39], [40]. Therefore, the confounding factor of language experience would have not influenced on validity of our conclusions.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…However, it is very unlikely that the vocalization-listening difference of ERPs would be specific to participants’ language experience. Several recent neurophysiological studies have demonstrated that cortical responses to mid-utterance PSS during active vocalization are enhanced relative to passive listening in either English or Mandarin participants [28], [29], [39], [40]. Therefore, the confounding factor of language experience would have not influenced on validity of our conclusions.…”
Section: Discussionmentioning
confidence: 63%
“…This confound leaves open a possibility that suppression or enhancement induced by vocalization observed in the present study may be related to the factor of temporal predictability. In a similar study that manipulating the timing of pitch shifts at mid-utterance as predictable or unpredictable [39], vocalization-induced suppression was found when the timing of pitch shifts was predictable, while enhancement effect was observed if subjects failed to predict their timing. This finding provides supportive evidence that suppression or enhancement of vocalization-induced responses to pitch shifts at mid-utterance is partly caused by the temporal predictability of feedback changes.…”
Section: Discussionmentioning
confidence: 93%
“…Upon the display of the group choice, the participants also found out whether their opinions were in conflict with the group members' opinion. We hypothesized that if a conflict of opinions in a group signals motivationally significant outcomes for future action, then FRN would be observed in the majority and the minority conditions, as shown in previous studies (Chen et al., ). In addition, if the majority rule influenced the evaluation of the conflict, then FRN or P300 components would be modulated in the minority condition.…”
Section: Outcome Evaluation In the Social Contextmentioning
confidence: 80%
“…Chen et al. () demonstrated that conflicts with other members in a line judgment task triggered FRN and that the amplitude of FRN reflected the level of the conflict, which was manipulated by the number of group members making different decisions from the participant's decision. Previous studies have investigated social conformity and normative group opinions with the decisions of confederates in a separate room that were used to elicit the conflict.…”
Section: Discussionmentioning
confidence: 99%
“…So far, only few studies in adults report a link between the FRN and subsequent behavior (Chen, Wu, Tong, Guan, & Zhou, 2012;Hämmerer et al, 2010;Mathewson, Dywan, Snyder, Tays, & Segalowitz, 2008;Cohen & Ranganath, 2007). To our knowledge, Cohen and Ranganath (2007) were the first to report empirical evidence for the hypothesis that neural feedback processing, as indicated by the FRN, is related to feedbackguided behavior.…”
Section: Functionality Of the Developing Feedback Processing Systemmentioning
confidence: 93%